Simulation Platforms in CT and MR Education: A Systematic Review. - Hadi, Yasser H.; Osman, Hamid (Radiologic Science & Education, 2026)
Simulation-based education (SBE) is increasingly used in radiologic technology training for computed tomography (CT) and magnetic resonance (MR) imaging to address limited clinical exposure. This systematic review identified six studies evaluating virtual platforms, including high-fidelity CT simulators, cloud-based systems, and MR software. Findings indicated improvements in technical skills, procedural accuracy, confidence, and preparedness, with some evidence of enhanced knowledge retention. However, studies were small, heterogeneous, and relied heavily on self-reported outcomes, with limited follow-up and no cost-effectiveness analyses. Overall, virtual simulation should complement, not replace, clinical training. Further research is needed to establish standardized metrics and assess long-term outcomes.